Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine the polynomial function \( f(x) \) with the specified characteristics, let’s go through the analysis step-by-step:
### Step 1: Identifying the Roots and Their Multiplicities
Given the roots and their multiplicities:
- Root at \( x = -4 \) with multiplicity 1
- Root at \( x = 5 \) with multiplicity 1
- Root at \( x = 1 \) with multiplicity 2
The general form of \( f(x) \) can be written as:
[tex]\[ f(x) = a(x + 4)(x - 5)(x - 1)^2 \][/tex]
where \( a \) is a constant multiplier that needs to be determined.
### Step 2: Utilizing the Y-Intercept
We know that the y-intercept of the function occurs when \( x = 0 \).
Given that the y-intercept is 40, we have:
[tex]\[ f(0) = 40 \][/tex]
### Step 3: Substitute \( x = 0 \) into the Polynomial
[tex]\[ f(0) = a(0 + 4)(0 - 5)(0 - 1)^2 \][/tex]
[tex]\[ f(0) = a \cdot 4 \cdot (-5) \cdot 1 \][/tex]
[tex]\[ 40 = a \cdot 4 \cdot (-5) \][/tex]
[tex]\[ 40 = a \cdot (-20) \][/tex]
[tex]\[ a = \frac{40}{-20} \][/tex]
[tex]\[ a = -2 \][/tex]
### Step 4: Construct the Polynomial with the Determined Multiplier
Now, substitute \( a = -2 \) back into the polynomial:
[tex]\[ f(x) = -2(x + 4)(x - 5)(x - 1)^2 \][/tex]
### Step 5: Expand the Polynomial Expression
Expand the expression to find the polynomial in standard form:
[tex]\[ f(x) = -2(x + 4)(x - 5)(x - 1)^2 \][/tex]
First, expand \( (x - 1)^2 \):
[tex]\[ (x - 1)^2 = x^2 - 2x + 1 \][/tex]
Next, expand \( (x + 4)(x - 5) \):
[tex]\[ (x + 4)(x - 5) = x^2 - x - 20 \][/tex]
Now, multiply the expanded terms:
[tex]\[ f(x) = -2(x^2 - x - 20)(x^2 - 2x + 1) \][/tex]
Further expanding:
[tex]\[ (x^2 - x - 20)(x^2 - 2x + 1) = x^4 - 2x^3 + x^2 - x^3 + 2x^2 - x - 20x^2 + 40x - 20 \][/tex]
[tex]\[ = x^4 - 3x^3 - 17x^2 + 39x - 20 \][/tex]
Multiply by \(-2\):
[tex]\[ f(x) = -2(x^4 - 3x^3 - 17x^2 + 39x - 20) \][/tex]
[tex]\[ = -2x^4 + 6x^3 + 34x^2 - 78x + 40 \][/tex]
Thus, the polynomial function is:
[tex]\[ f(x) = -2x^4 + 6x^3 + 34x^2 - 78x + 40 \][/tex]
### Step 1: Identifying the Roots and Their Multiplicities
Given the roots and their multiplicities:
- Root at \( x = -4 \) with multiplicity 1
- Root at \( x = 5 \) with multiplicity 1
- Root at \( x = 1 \) with multiplicity 2
The general form of \( f(x) \) can be written as:
[tex]\[ f(x) = a(x + 4)(x - 5)(x - 1)^2 \][/tex]
where \( a \) is a constant multiplier that needs to be determined.
### Step 2: Utilizing the Y-Intercept
We know that the y-intercept of the function occurs when \( x = 0 \).
Given that the y-intercept is 40, we have:
[tex]\[ f(0) = 40 \][/tex]
### Step 3: Substitute \( x = 0 \) into the Polynomial
[tex]\[ f(0) = a(0 + 4)(0 - 5)(0 - 1)^2 \][/tex]
[tex]\[ f(0) = a \cdot 4 \cdot (-5) \cdot 1 \][/tex]
[tex]\[ 40 = a \cdot 4 \cdot (-5) \][/tex]
[tex]\[ 40 = a \cdot (-20) \][/tex]
[tex]\[ a = \frac{40}{-20} \][/tex]
[tex]\[ a = -2 \][/tex]
### Step 4: Construct the Polynomial with the Determined Multiplier
Now, substitute \( a = -2 \) back into the polynomial:
[tex]\[ f(x) = -2(x + 4)(x - 5)(x - 1)^2 \][/tex]
### Step 5: Expand the Polynomial Expression
Expand the expression to find the polynomial in standard form:
[tex]\[ f(x) = -2(x + 4)(x - 5)(x - 1)^2 \][/tex]
First, expand \( (x - 1)^2 \):
[tex]\[ (x - 1)^2 = x^2 - 2x + 1 \][/tex]
Next, expand \( (x + 4)(x - 5) \):
[tex]\[ (x + 4)(x - 5) = x^2 - x - 20 \][/tex]
Now, multiply the expanded terms:
[tex]\[ f(x) = -2(x^2 - x - 20)(x^2 - 2x + 1) \][/tex]
Further expanding:
[tex]\[ (x^2 - x - 20)(x^2 - 2x + 1) = x^4 - 2x^3 + x^2 - x^3 + 2x^2 - x - 20x^2 + 40x - 20 \][/tex]
[tex]\[ = x^4 - 3x^3 - 17x^2 + 39x - 20 \][/tex]
Multiply by \(-2\):
[tex]\[ f(x) = -2(x^4 - 3x^3 - 17x^2 + 39x - 20) \][/tex]
[tex]\[ = -2x^4 + 6x^3 + 34x^2 - 78x + 40 \][/tex]
Thus, the polynomial function is:
[tex]\[ f(x) = -2x^4 + 6x^3 + 34x^2 - 78x + 40 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.